Phytochemical studies and the bioactivities of compounds from Ochrosia oppositifolia, Rauvolfia reflexa and Actinodaphne machrophylla / Mehran Fadaeinasab - Fadaeinasab, Mehran (2014)

(untitled)
The chemical constituents of Ochrosia oppositifolia, Rauvolfia reflexa (Apocynacea) and Actinodaphne machrophylla (Lauracea) have been studied. The compounds were extracted from the bark and leaves of the plants using n-hexane, dichloromethane and methanol as solvents. The crudes were subjected to extensive chromatographic techniques such as column chromatography (CC), preparative thin layer chromatography (PTLC), and high performance liquid chromatography (HPLC). Structural elucidation was established through several spectroscopic methods, such as 1D-NMR (1H, 13C, DEPT, NOE), 2D-NMR (COSY, NOESY, HMQC, and HMBC), UV, IR, and MS (GCMS, LCMS and HREIMS) and comparison with the published data. In this study, a total of twenty eight known and new compounds were isolated. Three known indole alkaloids namely isoreserpiline (120), neisosposinine (121) and reserpinine (122) were isolated from the bark of Ochrosia oppositifolia. Ten indole alkaloids and one β- carboline alkaloid were obtained from the bark of Rauvolfia reflexa, these are rauvolfine B (123), rauvolfine C (124) vinorine (125), rescinnamine (126), cantleyine (127), akuammilan-17-oic acid, 1,2-dihydro-3-hydroxy-1-methyl-, methyl ester (128), undulifoline (129), macusine B (130), isoreserpiline (120), akuammilan-17-oic acid, 12-hydroxy-, methyl ester (131) among these rauvolfine B (123) and rauvolfine C (124) appeared to be new. In addition, six known phenolic compounds and one new β- carboline alkaloid were isolated from the leaves of Rauvolfia reflexa namely 17-methoxy-carbonyl-14- heptadecaenyl- 4-hydroxy-3-methoxy cinnamate (132), 3-methyl-10,11-dimethoxyl-6-methoxycarbonyl- β- carboline (133), (E)-methyl 3-(4-hydroxy-3,5-dimethoxyphenyl) acrylate (134), 1,2,3,4- tetrahydro -1- oxo-β- carboline (135), 3-hydroxy-β-carboline (136), (E)-3-(3,4,5-trimethoxyphenyl) acrylic acid (137) and benzenepropanoic acid, 3- methoxy ii (138). 17-methoxy-carbonyl-14- heptadecaenyl- 4-hydroxy-3-methoxy cinnamate (132), and 3- methyl-10, 11-dimethoxyl-6- methoxycarbonyl- β- carboline (133) were the new compounds isolated from the leaves of Rauvolfia reflexa. The bark of Actinodaphne machrophylla has afforded eight known isoquinoline alkaloids, cycleanine (139), (-) -10-demethylxylopinine (140), reticuline (141), (+) - laurotetanine (142), (+) - bicuculine (143), (-) α- hydrastine (144), (+) - parafumine (145) and (+) - anolobine (146). Six samples from the bark and leaves of ochrosia oppositifolia including three crude extracts and three indole alkaloids and eight isoquinoline alkaloids from the bark of Actinodaphne machrophylla have been tested for their in-vitro inhibitory activity against P. falciparum 3D7. Among the crude extracts of Ochrosia oppositifolia dichloromethane crude extract of bark showed the most potent inhibitory activity, with the IC 50 value of 0.05051 μg/mL, the other crude extracts and compounds showed weak or no inhibitory activity against P. falsiparum as compare as standard which is chloroquine. Three indole alkaloids isolated from the bark of Ochrosia oppositifolia and eight isoquinoline alkaloids isolated from the bark of Actinodaphne machrophylla showed moderate in vitro antiplasmodial activities against Plasmodium falciparum 3D7 with the IC50 of 0.29 μM, 0.75 μM and 1.13 μM for isoreserpiline (120), neisosposinine (121), reserpinine (122) and 0.08 μM, 1.18 μM, 3.11 μM, 0.65 μM, 0.26 μM, 3.99 μM and 1.38 μM for cycleanine (139), (-) -10-Demethylxylopinine (140), reticuline (141), (+) - laurotetanine (142), (+) – bicuculine (143), (-) - a- hydrastine (144), (+) - parfumine (145) and (+) - anolobine (146) respectively which are comparible with standard chloroquine. Antialzheimer activity of crude extracts and pure compounds isolated from the leaves and the bark of Rauvolfia reflexa was carried out. The dichloromethane and ethanol crude iii extracts of the leaves and methanol crude extract of the bark exhibited good inhibitory activity against both enzymes, while the methanol crude extract of the leaves showed moderate inhibitory activity against acetylcholinesterase (AChE). Cytotoxic effects of rauvolfine B (123), macusine B (130) and isoreserpiline (120) against different cancer and normal cell lines were determined. At the tested concentrations (1.5 – 250 μM), macusine B (130) and isoreserpiline (120) did not effectively suppress the cell proliferations of cancer cells. Rauvolfine B (123) revealed moderate cytotoxic effects against two breast cancer cells (MCF-7 and MDA-MB-231) and colon cancer cells (HT-29). However, test on colon cancer cells (HCT-116), rauvolfine B (123) elicited the strongest cytotoxic effect with IC50 value of 46.86, 39.93 and 33.38 μM after 24, 48 and 72 h of treatment respectively. Rauvolfine B (123) was selected for further study on the possible mechanism as it shown potential activity activity against HCT-116 cell line. Morphological changes in the treated HCT-116 cells with rauvolfine B (123) were observed under fluorescent microscope. After 24 h, apparent marks of apoptosis, such as membrane blebbing and cytoplasmic shrinkage were noted at IC50 dose of rauvolfine B (123).